An investigation of some motoric characteristics of national elite wrestling athletes - Tutar, M.; Biyikli, T.; Ildem, C.; Ilhan, M. (Science, Movement & Health, 2024)
Aim. This study reveals the data of the analysis of the motoric characteristics of thirty National A wrestling athletes, ten Greco-Roman, ten freestyle and ten female. Methods. The study included 10 national wrestling athletes, 10 freestyle and 10 female National A wrestling athletes. Results. These data show a high level of training of the athletes and confirm the specificity of these tests for single fights. The applied tests are informative for the estimation of the functional state of athletes. The dynamics of their results gives the necessary information to predict the success of athletes and can be used in monitoring their condition. Conclusions. As a result of the tests performed in elite athletes, it is recommended to give special exercise movements for muscle groups with muscle imbalances.